Practicing the Patience of God: A Response to Technologically Induced Impatience by Way of Ancient Holy Habit. Issue 2 (November 2019) - Baker, Samuel E.
This article addresses three interrelated concerns: the pervasive nature of technologically induced impatience, a theological understanding of divine patience, and, finally, a suitable response to techno-impatience by way of engagement with the art and practice of holy habit. As we have experienced faster flows of information, and larger amounts of information through which we must sort, we have become less patient people. This loss of patience continues to produce a new kind of personal and communal disquiet on an impressive scale. To address concerns with techno-impatience, arguments will be drawn from scriptural and theological concepts of divine patience. These concepts prompt us to rediscover, and reinvent, a richer understanding of patience as an individuated spiritual virtue. Accordingly, a corrective to the exacerbating effects of technologically induced impatience will be offered: namely, the explicit spiritual discipline of practicing holy patience.